Two new species of Agaporomorphus Zimmermann (Coleoptera: Dytiscidae) from Peru - Miller, Kelly B. (Zootaxa, 2005)
Two new species in the genus Agaporomorphus Zimmermann are described from Madre de Dios, Peru, A. tambopatensis Miller, n. sp. and A. silvaticus Miller, n. sp. A key to males of all the species in the genus is provided. A cladistic analysis is presented including the new species. Agaporomorphus is arranged into three species groups; the A. dolichodactylus-group (A. dolichodactylus Miller, A. mecolobus Miller and A. grandisinuatus Miller); the A. knischi-group (A. knischi Zimmermann, A. tambopatensis and A. silvaticus); and the A. pereirai-group with a single species, A. pereirai Guignot. Taxonomically and phylogenetically important characters are discussed and illustrated.